2019
DOI: 10.1002/ange.201905949
|View full text |Cite
|
Sign up to set email alerts
|

Expanding APEX2 Substrates for Proximity‐Dependent Labeling of Nucleic Acids and Proteins in Living Cells

Abstract: The subcellular organization of biomolecules such as proteins and nucleic acids is intimately linked to their biological functions.A PEX2, an engineered ascorbate peroxidase that enables proximity-dependent labeling of proteins in living cells,has emerged as apowerful tool for deciphering the molecular architecture of various subcellular structures.However,only phenolic compounds have thus far been employed as APEX2 substrates,and the resulting phenoxyl radicals preferentially react with electron-rich amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Excitingly, the labeling of RNA by APEX enzymes is enabling the parallel probing of RNA and protein proximity interactomes, as recently reported by the Ting and Ingolia groups (122)(123)(124). Furthermore, aromatic substrate exploration identified that biotin-aniline and biotin-naphthylamine are preferentially transferred to RNA and DNA in comparison to biotin-phenol (125), providing new avenues of exploration for the APEX-seq modalities described below. This type approaches should enable a better understanding of the protein-nucleic acid interactions.…”
Section: Protein-nucleic Acid Contactsmentioning
confidence: 84%
“…Excitingly, the labeling of RNA by APEX enzymes is enabling the parallel probing of RNA and protein proximity interactomes, as recently reported by the Ting and Ingolia groups (122)(123)(124). Furthermore, aromatic substrate exploration identified that biotin-aniline and biotin-naphthylamine are preferentially transferred to RNA and DNA in comparison to biotin-phenol (125), providing new avenues of exploration for the APEX-seq modalities described below. This type approaches should enable a better understanding of the protein-nucleic acid interactions.…”
Section: Protein-nucleic Acid Contactsmentioning
confidence: 84%
“…1a ). In addition, we also synthesized BN1 and BN2 with aromatic amine structures as reported recently by us with weak protein labeling activity 18 . The general rationale for selecting these probes is that the bond dissociation energy (BDE) of the -OH bond and -NH 2 bond of the benzene ring could be modulated by introducing chemical substituent 13 , 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been predicted that the labeling radius of the biotin-phenol radical and therefore the labeling specificity of APEX-based proximity labeling could be modulated by modifying the aromatic ring with chemical substituents, and this approach has confirmed the robust proximity labeling of subproteome by biotin-phenol and leaded to the recent development of highly efficient APEX-based RNA labeling 13 , 18 . In this study, we design a series of biotin-phenol analogs by modifying the phenolic hydroxyl structure.…”
Section: Introductionmentioning
confidence: 95%
“…APEX2 has attracted much attention as a powerful tool for protein interaction analysis, and its applications include revealing proteomes in subcellular compartments [51,52,62,63,64,65], G-protein-coupled receptor complexes [66,67], subcellular transcriptome mapping [68,69], and APEX2-proximity RNA labeling [70,71].…”
Section: Peroxidase-proximity Protein Labelingmentioning
confidence: 99%